Peran Fear of Missing Out Memediasi Pengaruh Promo Event Tanggal Kembar E-Commerce Shopee Terhadap Impulsive Buying Tendency Pada Generasi Z Pengguna Shopee di Bandar Lampung - Rini Wijaningsih; Evi Ekawati; Adib Fachri (GEMILANG: Jurnal Manajemen dan Akuntansi, 2024)
Fear of missing out is the fear of losing the opportunity to follow something that they think is interesting to follow such as the shopee e-commerce twin date event promo by offering attractive discount products that occur every month on the same date, so that it can encourage someone to make a purchase that was not planned before. This study aims to show how much the level of impulsive buyimg behavior of Gen Z in Bandar Lampung is caused by the shopee e-commerce twin date promo event and through fear of missing out as mediation. The research method used is quantitative method with a research population of 296,828 thousand residents and a sample size of 100 respondents. The results showed that the shopee e-commerce twin date promo event had a significant positive effect on impulsive buying tendency and the fear of missing out variable had a positive and significant effect and mediated the relationship between the shopee e-commerce twin date promo event and impulsive buying tendency. The results of research in an Islamic business perspective regarding impulsive buying tendency behavior in Islamic consumption theory that Islam prohibits anything excessive and must adhere to the principles of simplicity and balance.